Analysis of serum glutamic pyruvic transaminase and serum glutamic oxaloacetic transaminase levels in tuberculosis patients who are undergoing oat treatment in Kendari City General Hospital, Kota Kendari, Indonesia - Sri Anggarini Rasyid; Armayani; Yuniati; Tiara Mayang Pratiwi Lio (MDPI AG, 2020)
In the treatment of tuberculosis (TB), the patient is generally directly given Anti Tuberculosis Drugs (Obat Anti Tuberculosis/OAT) without examining Serum Glutamic Pyruvic Transaminase (SGPT) and Serum Glutamic Oxaloacetic Transaminase (SGOT) to see whether or not there is liver damage before treatment. Because of the side effects by OAT, it is important to know how the condition of the liver function of TB patients who consume OAT in Kendari City General Hospital (Rumah Sakit Umum Daerah/RSUD) Kota Kendari by looking at SGOT and SGPT levels in order to provide maximum treatment to TB patients. The method of this research was descriptive analysis with cross sectional approach. The sample is all patients had previously been diagnosed with TB by a doctor based on medical records by in RSUD Kota Kendari after 1-2 months OAT treatment without any sign of liver injury before. Examination of SGOT and SGPT levels was performed on all samples in the Laboratory of RSUD Kota Kendari using clinical chemistry analyzer. The results of this study showed that 20% patients with TB had elevated levels of SGPT and SGOT with average SGOT is 51 U/L and SGPT is 42.5. The Inference of this study that there is an increase in SGOT and SGPT levels in patients who consume OAT 1-2 months in RSUD Kota Kendari. Elevated levels of SGPT and SGOT due to Anti Tuberculosis (OAT) drugs did not occur in all patients and only increased in 3 people, but qualitatively the effect of administering anti-tuberculosis drugs significantly increased levels of SGPT and SGPT. Thus, monitoring of liver physiology remains recommended especially for elderly patients.